Fairness - Glassman, Bruce; Josephson Institute for the Advancement of Ethics ([San Diego, Calif.] : Bearing Books, 2008)
Teaches children the importance of fairness, explaining what it means to be fair, how fairness impacts people's lives, and other related topics.
What is fairness? -- The importance of fairness -- Fairness in your life.
"Josephson Institute Character Counts.".
Includes bibliographical references (p. 47) and index.
6.4
3-6
Keywords: Fairness -- Juvenile literature; Fairness; Fairness; Fairness